Sales trends of psychotropic drugs in the COVID-19 pandemic: A national database study in Brazil - Del Fiol, Fernando de Sá; Bergamaschi, Cristiane de Cássia; Lopes, Luciane Cruz; Silva, Marcus Tolentino; Barberato-Filho, Silvio (Frontiers in Pharmacology, 2023)
Abstract [Background]: The social restrictions among coronavirus disease 2019 (COVID-19) pandemic have posed a thoughtful risk to mental health and have implications in the use of drugs, including antidepressants, anxiolytics and other psychotropics. [Objective]: This study analyzed the sales data of the psychotropics prescribed in Brazil, in order to verify the change in consumption trends of these drugs during the COVID-19 pandemic. [Methods]: This interrupted time-series analyzed psychotropic sales data, between January 2014 and July 2021, using the National System of Controlled Products Management from The Brazilian Health Regulatory Agency. The monthly mean DDDs per 1,000 inhabitants per day of psychotropic drugs was evaluated by analysis of variance (ANOVA) followed by Dunnett Multiple Comparisons Test. The changes in monthly trends in the use of the psychotropic studied were evaluated by Joinpoint regression. [Results]: During the period studied, clonazepam, alprazolam, zolpidem and escitalopram were the most sold psychotropic drugs in Brazil. According to Joinpoint regression, an upward trend was observed in sales during the pandemic of pregabalin, escitalopram, lithium, demvefaxine, citalopram, buproprion and amitriptyline. An increase in psychotropic consumption was noted throughout the pandemic period, with the maximum consumption (2.61 DDDs) occurring in April 2021, with a downward trend in consumption that accompanied the drop in the number of deaths. [Conclusions]: The increase in sales, mainly of antidepressants during the COVID-19 pandemic, draws attention to issues related to the mental health of the Brazilian population and on the need for greater monitoring in the dispensing of these drugs.